ANTLERS GROWTH OF THE ENDANGERED AND ENDEMIC BAWEAN DEER (Axis kuhlH Muller & Schlegel, 1842) - Semiadi, Gono; Subekti, Koestoto; Sutama, I Ketut; Affandy, Lukman (TREUBIA, 2003)
Bawean deer (Axis kuhlii) is an endangered Indonesian deer that is quite unique since its habitat is isolated and the species is endemic to the Bawean Island. Data on its biology is very limited. especially those related to antlers growth. Monitoring the antlers growth from the post weaning age (3-4 months) to 22 months old showed that, this process was related to the animals reproductive physiology, starting at the age of six months, when the testes entered the scrotum. and a rapid body growth occured. At the age of 21 months, the animal had its first full hard antlers. The stag had its longest period of hard antlers at least for more than eight months. There seemed to be a close relation between the body growth cycles and theantlers growth. Hair molting lasted for 25-40 days. These results indicated that the period of physiological change in relation to antlers growth and some reproductive activities in the Bawean deer were within the cycle of other temperate and tropical deer species.Key words: Bawean deer, Axis kuhlii, antlers growth, molting